Maj. T.R. White and M/Sgt Sam Haddad at NCO ""March of Dimes"" Dance
Maj. T.R. White and M/Sgt Sam Haddad at NCO ""March of Dimes"" Dance. From the collection of Robert H. Bensing. Gift of Tim Bensing.